Advances and Novel Treatment Options in Metastatic Melanoma - Facchiano, Antonio; Del Bufalo, Donatella; Carè, Alessandra (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book presents several studies reporting advances on melanoma pathogenesis, diagnosis and therapy. It represents a milestone on the state of the art, updated at 2021, and also presents the current knowledge on the future developments in melanoma field.